Anarchism and the Avant-Garde : radical arts and politics in perspective - Kosuch, Carolin, 1981- (Leiden ; Boston : Brill Rodopi, 2020)
Anarchism and the Avant-Garde: Radical Arts and Politics in Perspective contributes to the continuing debate on the encounter of the classical anarchisms (1860s−1940s) and the artistic and literary avant-gardes of the same period, probing its dimensions and limits. Case studies on Dadaism, decadence, fauvism, neo-impressionism, symbolism, and various anarchisms explore the influence anarchism had on the avant-gardes and reflect on avant-garde tendencies within anarchism. This volume also explores the divergence of anarchism and the avant-gardes. It offers a rich examination of politics and arts, and it complements an ongoing discourse with theoretical tools to better assess the aesthetic, social, and political cross-pollination that took place between the avant-gardes and the anarchists in Europe.--
Introduction / Carolin Kosuch -- 1. Frictions: Aesthetics or Politics. The Symbolist Movement: Anarchism and the Avant-Garde in Fin de Siècle France / Richard Shryock -- Egoism, Homosexuality, and Joie de vivre: Jacob Epstein's Tomb of Oscar Wilde / Mark Antliff -- A Politics of Technique: Fauvism and Anarchist Individualism / Patricia Leighten -- Anti-Art? Dada and Anarchy / Daniela Padularosa -- 2. Fractions: Declining, Pioneering, Redeeming. Decadent Anarchism, Anarchistic Decadence: Contradictory Cultures, Complementary Politics / David Weir -- 'We Are Too Far Ahead to be Understood': Vanguard Creation in Fin de Siècle Anarchism / Carolin Kosuch -- 'Theocratic Anarchism'? Walter Benjamin and Gershom Scholem in Switzerland: Anarchism, Messianism and the Avant-Garde / Gabriele Guerra -- 3. Focal Points: Art and Education in Local and Transnational Settings -- Syndicalism and Art in France before 1914: Propaganda and Prefiguration / Constance Bantman -- Anarchism, Geography and Painting: Élisée Reclus and Social Art / Federico Ferretti -- Teaching Revolution through Art? Anarchism, the Avant-garde and Education Critically Revisited / Piotr Laskowski.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Avant Garde; Avant-garde (Aesthetics) -- Political aspects; Anarchism and art; Arts -- Political aspects; Art -- Political aspects; Avant-garde (Aesthetics) -- History -- 19th century; Avant-garde (Aesthetics) -- History -- 20th century; Anarchism -- History; Anarchists; Anarchisme -- Histoire; Anarchisme et art; Arts -- Aspect politique; Anarchistes; anarchism; anarchists; Anarchism; Anarchismus; Gesellschaftskritik; Künste; Kunst; Literatur; Regelverstoß; History